Enhanced photovoltaic performance of PEDOT:PSS/Si solar cells using hierarchical light trapping scheme. (August 2018) - Singh, Prashant; Srivastava, Sanjay K.; Sivaiah, B.; Prathap, P.; Rauthan, C.M.S.
Highlights: Hierarchical light trapping scheme is proposed for PEDOT:PSS/Si hybrid solar cells. Excellent omnidirectional light trapping is demonstrated in broad spectral range. Power conversion efficiency (PCE) >10.25% is demonstrated for optimal structuring. Significant enhancement in PCE > 0.75% as compared to control hybrid cell is achieved. Co-relation of microstructural, optical and electrical properties of devices is analyzed. Abstract: Organic-inorganic hybrid solar cells have attracted tremendous research attention in recent years owing to their low fabrication cost and potentially high performance. In the present study, hierarchical structures consisting of nanostructures made over micro-textured pyramidal (MPs) silicon surface are used in PEDOT:PSS/Si heterojunction solar cells to achieve a power conversion efficiency (PCE) up to 10.26%. The combined micro-nanostructuring concept provides a superior light trapping ability (compared to only micro-textured Si), mechanical stability (compared to only Si nanowire arrays concept), increased junction area and hence improved photovoltaic (PV) characteristics including short-circuit photocurrent and PCE. Silver assisted electroless wet chemical etching is used to produce nanostructures of different length over the micro-pyramidal Si. The hierarchically structured surfaces have one-fourth reflectance in broad spectral range (300–1100 nm) as compared to micro-pyramidal Si (∼13%) arising from the enhanced light trapping properties of nanostructures owing to multiple interaction of incident light and dimensions equivalent to sub-wavelength structures. Moreover, the hierarchical structures exhibit excellent omnidirectional light trapping ability at wide range of angle of incidence of light and spectral wavelength, which is essential for practical PV applications. This has been demonstrated using solar weighted reflectance corresponding to AM 1.5G solar flux and compared with that of MPs surface. Influence of nanostructuring time on reflectance and PV performance of the solar cell has been investigated. A significant enhancement in PCE up to 0.78% (absolute) and over 8.0% (relative) could be achieved as compared to MPs-Si based hybrid solar cell (control cell) for an optimized hierarchically structured Si surfaces. It is established that an optimal trade-off between reduced reflectance of such surfaces and solar cell performance parameters is essential. Longer nano-structuring despite exhibiting a better light trapping properties results in poor cell efficiency as the nano-structuring also leads to increased surface area and non-conformal coating of the polymer. Hence, increase in photocurrent is also accompanied by a simultaneous deterioration of other cell parameters such as open circuit voltage and fill factor of the device. Nevertheless, a properly designed hierarchical-structured device paves a promising way for developing low-cost and efficient PV applications in the future.